The Effect of Progressive Muscle Relaxation on Anxiety among Cancer Patients Undergoing Chemotherapy - Febriana Sartika Sari; Selma Andina; Insiyah Insiyah; Siti Lestari; Michael John Flores (Jurnal Penelitian Perawat Profesional, 2026)
Cancer is a serious disease that causes mortality globally. Cancer patients who undergo chemotherapy frequently experience anxiety. Anxiety may arise from uncertainty regarding treatment outcomes, fear of disease progression, side effects of chemotherapy, and changes in physical and social functioning. Non-pharmacological interventions such as Progressive Muscle Relaxation (PMR) are increasingly recommended. The research objective is to identify the influence of PMR on the level of anxiety among cancer patients undergoing chemotherapy. The research method used quantitative pre-experimental design without control group. The research was carried out among 31 cancer patients undergoing chemotherapy who were selected using purposive sampling technique. Anxiety levels were measured using the Zung Self-Rating Anxiety Scale (ZSAS). PMR was administered twice daily for three days. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of 5%. The research result showed before the intervention, most of respondents had mild anxiety (74.2%), while 25.8% had moderate anxiety. Following PMR, 74.2% of respondents were categorized having normal anxiety levels and 25.8% in the mild anxiety category. Statistical analysis demonstrated a significant reduction in anxiety after PMR (Z = -4.874; p = 0.000). The conclusion is PMR significantly reduced anxiety levels among patients with cancer undergoing chemotherapy. PMR may be considered an effective nursing intervention to decrease anxiety among cancer patients receiving chemotherapy.